2010
DOI: 10.1080/00909881003639510
|View full text |Cite
|
Sign up to set email alerts
|

Connection, Restructuring, and Buffering: How Groups Link Individuals and Organizations

Abstract: Research examining the individualÁorganization relationship has largely ignored the linking role of groups. Grounded in Scott, Corman, and Cheney's (1998) structurational model of organizational identification, we analyzed data obtained from members of groups embedded in a large religious organization. Results revealed three primary ways groups link individual members and the organization via identification. The connection function provides members with local copresent linkages to the organization and an envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Group connections aid in organizational and professional identity construction and maintenance. These connections also provide protection from negative aspects of organizational identity (Silva & Sias, 2010). SD's detrimental effect on relationships, however, estranges individuals from the organization, so SD is expected to be negatively related to organizational identification.…”
Section: Downloaded By [Rutgers University] At 16:22 12 April 2015mentioning
confidence: 98%
See 1 more Smart Citation
“…Group connections aid in organizational and professional identity construction and maintenance. These connections also provide protection from negative aspects of organizational identity (Silva & Sias, 2010). SD's detrimental effect on relationships, however, estranges individuals from the organization, so SD is expected to be negatively related to organizational identification.…”
Section: Downloaded By [Rutgers University] At 16:22 12 April 2015mentioning
confidence: 98%
“…Identification, the extent to which an organizational member shares and expresses the organization's values and decision premises (Cheney & Tompkins, 1987), has long been linked to job satisfaction and employee commitment (Scott et al, 1999) across occupations, but has not been a focus in the nursing literature. An individual's identification with the organization is provided by group links; groups provide connection, identity restructuring, and buffering from undesirable aspects of organizational identity (Silva & Sias, 2010). Identification with one's organization and profession is likely related positively to job satisfaction and negatively to turnover in nursing.…”
Section: Sd and Variables Related To Job Satisfactionmentioning
confidence: 99%
“…Some studies suggest that communicative interactions in FBOs have constructive implications for members' various individual and organizational identities (e.g., Hoffman, 2007;Leeman, 2006;Silva & Sias, 2010). For example, Hoffman (2007) cited how Benedictine women helped each other to reconcile their organizational identities with the larger Roman Catholic Church.…”
Section: Intersections Of Multiple Identitiesmentioning
confidence: 95%
“…Scott et al, 1998). Silva and Sias (2010) recently offered an empirical study of this activityidentification link in FBOs, finding that organizational identification was fostered in group gatherings through the activities of connection and restructuring (providing opportunities for members to feel unified with the organization and share/reconcile alternative views of the organization respectively); alternatively, they concluded that buffering activities (providing opportunities to accept discordant views) spurred organizational disidentification. The present study goes beyond Silva and Sias's work to examine specific discursive features of group interactions and their links to organizational and individual (dis)identification, but before doing so I first sketch the scholarly understandings of FBOs as contexts for the identification process.…”
Section: Communicative Theories Of Organizational Identity/identificamentioning
confidence: 97%
See 1 more Smart Citation